The applicability and effectiveness of the cognitive behavioral therapy for insomnia (Smart CBT-I plus) online program in patients with insomnia disorder combined with anxiety and depression: a randomized controlled trial protocol - Yating Zhao; Fangmei Ge; Xin Luo; Jingru Li; Jing Zhang; Yi Ju; Jie Zhang; Yong Wang; Dongbin Lyu; Yiren Qiu; Chengmei Yuan (Frontiers in Psychiatry)
BackgroundInsomnia is often accompanied by depression and anxiety, which can seriously affect people’s quality of life. Cognitive behavioral therapy for insomnia (CBT-I) is the first-line treatment, but the existing CBT-I ignores the intervention for anxiety-depressive symptoms, and has poor efficacy due to the lack of artificial support, poor compliance, the inability to spread widely and high dropping rate. A balance is needed between the convenience and efficiency of web-based technology and patient needs. Again in this context, an online WeChat applet (Smart CBT-I plus) will be developed with CBT-I technology as the core, integrating cognitive behavioral intervention modules for depression and anxiety.ObjectivesThis study will validate the effectiveness and applicability of Smart CBT-I plus by examining whether the Smart CBT-I plus study group will significantly reduce the distress of people suffering from insomnia with anxiety and/or depression symptoms compared to the psychoeducational group.MethodsIn this parallel-group, randomized controlled trial, 180 patients seeking help for insomnia combined with anxiety and/or depression will be recruited, and they will be randomized with 60 patients being assigned to the psychoeducation group (control group), and 120 patients being assigned to the Smart CBT-I plus group (study group). Measurements will be taken at baseline, post-intervention, 6 and 12 month follow-up, at the same time, semi-structured qualitative interviews about the experience of using Smart CBT-I plus will be conducted with randomly selected patients from the study group.ResultsThe results will involve insomnia, depression and anxiety to explore its effectiveness, in-treatment dropout rates and subjective patient feedback to explore the applicability of Smart CBT-I plus.Future recommendationsSelf-help platforms need to be more individually designed to reach a wider audience. Research aimed at a wider audience, such as the general public, will make the research more universal and the platform more meaningful.